2006
DOI: 10.1364/ol.31.001402
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional imaging of atomic distribution morphology created by holographically induced mass transfer of monomer molecules and nanoparticles in a silica-nanoparticle-dispersed photopolymer film

Abstract: We report an electron-probe microanalysis of a hologram recorded in a silica-nanoparticle-dispersed photopolymer film. We used S and Si atoms as label elements to identify formed polymer and nanoparticle species, respectively. It is found that the periodic density distributions of S and Si atoms are out of phase with each other, indicating that those of the formed polymer and nanoparticles are out of phase each other. This result shows decisive evidence of the mutual diffusion of monomer molecules and silica n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 9 publications
2
38
0
Order By: Relevance
“…It has been previously shown [12][13][14][15][16][17][18][19][20][21][22] that the holographic recording process in nanoparticle doped photopolymerisable materials can lead to the redistribution of the nanoparticles and thus to the creation of patterns of particle rich and particle depleted areas ( Figure 1B). The diffraction efficiency, η, of such a volume phase hologram is given by (2):…”
Section: Theorymentioning
confidence: 89%
“…It has been previously shown [12][13][14][15][16][17][18][19][20][21][22] that the holographic recording process in nanoparticle doped photopolymerisable materials can lead to the redistribution of the nanoparticles and thus to the creation of patterns of particle rich and particle depleted areas ( Figure 1B). The diffraction efficiency, η, of such a volume phase hologram is given by (2):…”
Section: Theorymentioning
confidence: 89%
“…However, in order to develop photosensitive materials with advanced performance (higher ∆n), the research was oriented towards phototopolymers doped with dispersed nanoparticles during the last decades. Scientists displayed lots of imagination in investigating this approach; thus TiO 2 [3][4][5][6], SiO 2 [6][7][8][9][10], ZrO 2 [6,[11][12][13], ZrO 2 :Eu 3+ [14], LaPO 4 :Ce 3+ , Tb 3+ [15], LaPO 4 :Tb 3+ nanorods [16], silver [17,18] and gold nanoparticles [19], CdSe [20], CdSe/ZnS [21,22] and ZnO quantum dots (QDs) [23] were used more or less successfully. During the course of the recording process, nanoparticles were forced to diffuse away from the constructive to the destructive interference regions of the interference pattern [7,11,[15][16][17][18][19]21,24].…”
Section: Introductionmentioning
confidence: 99%
“…In this way nanocomposites material exhibiting remarkable optical [1], mechanical [2,3], electrooptical [4], thermal [5] and electrical [6] properties can be obtained with a high potential for new applications [7,8]. Recently, controllable incorporation of solid nanoparticles such as SiO 2 [9,10], TiO 2 [11,12] and ZrO 2 [13] in holographic photopolymers opens up the opportunity for optimization, improvement and further development of recording capabilities of widely used photopolymers. It has been shown that at optimum values of recording intensity and volume fractions of incorporated nanoparticles a redistribution of particles occurs leading to an increase of diffraction efficiency of the recorded gratings due to a higher refractive index modulation [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, controllable incorporation of solid nanoparticles such as SiO 2 [9,10], TiO 2 [11,12] and ZrO 2 [13] in holographic photopolymers opens up the opportunity for optimization, improvement and further development of recording capabilities of widely used photopolymers. It has been shown that at optimum values of recording intensity and volume fractions of incorporated nanoparticles a redistribution of particles occurs leading to an increase of diffraction efficiency of the recorded gratings due to a higher refractive index modulation [9][10][11][12][13]. The main issues arising in these hybrid systems are the compatibility between the polymer host and the dopants and the optical losses due to scattering that increases with the size of nanoparticles and the difference between the nanoparticle refractive index and that of the photopolymer matrix.…”
Section: Introductionmentioning
confidence: 99%